Does quality help the financial viability of hospitals? A data envelopment analysis approach. (February 2022) - Onder, O.; Cook, W.; Kristal, M.
Abstract: In this work, we analyze the financial viability of U.S. hospitals by investigating the impact of clinical and experiential quality as its determinants. We adopt Simar and Wilson's two-stage bootstrapped truncated regression approach. Specifically, we use data envelopment analysis (DEA) in the first stage to estimate efficiency scores. Then, we use truncated regression estimation with the double-bootstrap method to test the significance of the quality variables. Given the financial problems recently experienced by U.S. hospitals, we use readmission rates and costs as our outputs to investigate how well hospitals can lower readmission rates while minimizing their costs, since recent policy changes have tied a portion of hospital reimbursements to their readmission rates, making both variables crucial outcome goals. We find that both clinical and experiential quality are significantly associated with the higher financial viability of hospitals. Further, focusing on these two quality dimensions together has additional benefits. Highlights: We analyze the impact of clinical and experiential quality on the financial viability of U.S.hospitals. A financial viability definition for hospitals is proposed. We adopt Simar and Wilson's two-stage bootstrapped truncated regression approach. Both clinical and experiential quality are significantly associated with the higher financial viability of hospitals.